1990
DOI: 10.1116/1.576609
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface damage and contamination of silicon following electron cyclotron resonance etching

Abstract: Articles you may be interested inThermal anneal activation of near-surface deep level defects in electron cyclotron resonance hydrogen plasmaexposed silicon J. Vac. Sci. Technol. B 15, 226 (1997); 10.1116/1.589269 Damage and contamination in lowtemperature electron cyclotron resonance plasma etching Damage formed by electron cyclotron resonance plasma etching on a gallium arsenide surface Damage and contamination produced after electron cyclotron resonance (ECR) etching of Si using CF 4 gas has been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…22 The length of the ECR source is 39 cm; the diameter and length of the RIE chamber are 48 and 51 em, respectively. The inner diameter of the ECR source is 13.2 cm when an anodized aluminum liner is used.…”
Section: M3mentioning
confidence: 99%
“…22 The length of the ECR source is 39 cm; the diameter and length of the RIE chamber are 48 and 51 em, respectively. The inner diameter of the ECR source is 13.2 cm when an anodized aluminum liner is used.…”
Section: M3mentioning
confidence: 99%
“…1,2 Oehrlein et al have found that two nearsurface damage layers were formed under a fluorocarbon film deposited on the surface. It is known, however, that RIE induced damage and contamination occur when Si substrates are exposed to a high flux of energetic ion bombardment in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…3 The competition between creation and removal of damage by dry etching determines whether the devices will have low damage or not. 6,9,10 Slow etching of Si has been shown to lead to accumulation of damage 10,11 while faster etch rates for GaAs have been shown to lead to a denser but shallower damage layer near the surface. 6 Etching damage extends deeper than the predicted ion stopping range due to both defect diffusion [7][8][9]12 and ion channeling 8,13 during etching.…”
Section: Introductionmentioning
confidence: 99%